Bosnia and Herzegovina – Unfortunate Country (Czech Journal of International Relations, 2024)
Ladislav Hladký: Bosna a Hercegovina. Historie nešťastné země. Nakladatelství Doplněk, Brno 1996, 216 stran, ISBN 80-85765-61-6.